PUDARNYA SIKAP ATAU PERILAKU MASYARAKAT INDONESIA DALAM KONTEKS BERSOSIALISASI - Suhernita Suhernita; Susi Mastuliana; Siti Suleho; Ryan Ramadhan (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research is an effort to preserve and foster a sense of love for traditional culture by preserving traditional art to realize the resilience of conventional culture. Culture is the legacy of our ancestors passed down from generation to generation and must be maintained. We as the next generation must participate in preserving and maintaining the culture we have so that it is not lost due to changes in the 6 eras. Moreover, in the era of society 5.0, we can easily utilize technology to preserve traditional culture so that it can be known and studied by the public, especially in Indonesia.